2021
DOI: 10.1016/j.envres.2021.111309
|View full text |Cite
|
Sign up to set email alerts
|

Performance study of a sterilization box using a combination of heat and ultraviolet light irradiation for the prevention of COVID-19

Abstract: SARS-CoV-2 virus and other pathogenic microbes are transmitted to the environment through contacting surfaces, which need to be sterilized for the prevention of COVID-19 and related diseases. In this study, a prototype of a cost-effective sterilization box is developed to disinfect small items. The box utilizes ultra violet (UV) radiation with heat. For performance assessment, two studies were performed. First, IgG (glycoprotein, a model protein similar to that of spike glycoprotein of SARS-COV-2) was incubate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…Generally, the median half-life of the novel Coronavirus in aerosol is 2.74 h. It can live on contaminant surfaces for up to several days and still be infectious. Consequently, a combination of heat and ultraviolet light irradiation was used for the sterilization and prevention of COVID-19 ( Mahanta et al, 2021 ). However, our studies didn't observe a significant difference of solar radiation at low- and high-altitude regions.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the median half-life of the novel Coronavirus in aerosol is 2.74 h. It can live on contaminant surfaces for up to several days and still be infectious. Consequently, a combination of heat and ultraviolet light irradiation was used for the sterilization and prevention of COVID-19 ( Mahanta et al, 2021 ). However, our studies didn't observe a significant difference of solar radiation at low- and high-altitude regions.…”
Section: Discussionmentioning
confidence: 99%
“… Liu et al (2021a) showed implications for COVID-19 related to the fact that selenium plays a key role in the biological effects of some viruses. Liu et al (2021b) reported the data of a study on the role of seasonality in the spread of COVID-19 pandemic, whereas Mahanta et al (2021) conducted a performance study of a sterilization box, using a combination of heat and ultraviolet light irradiation for the prevention of COVID-19. More general was the study by Moresco et al (2021) , dealing with the survival of human enteric and respiratory viruses on plastics in soil, freshwater, and marine environments, as was that conducted by Pirasteh-Anosheh et al (2021) , focused on haloculture as a system to mitigate the negative impacts of pandemics on the environment, society, and economy.…”
Section: Comments On Papers Published In the Virtual Speciasll Issuementioning
confidence: 99%
“…Typically, different kind of disinfectant techniques hydrogen peroxide vaporization, microwave generating steam, UV radiation and dry heating are available to stop the spreading of COVID19 ( Arellano-Cotrina et al, 2021 , Mahanta et al, 2021 , V, A.A.R., R, V., Haghighat, F., , 2020 ). Among different chemicals, 75% ethanol, peroxy-acetic acid, chloroform and other chlorine containing disinfectant (sodium hypo-chloride etc.)…”
Section: Introductionmentioning
confidence: 99%